The role of progesterone and the progesterone receptor in human reproduction and cancer. Issue 5 (September 2013) - Check, Jerome H; Cohen, Rachael
Insufficient progesterone, effect possibly more on immune factors rather than adequate endometrial development, can be an easy remedial cause of infertility by simply supplementing the luteal phase with either vaginal or intramuscular or oral (dydrogesterone) progesterone. Progesterone will also help to reduce miscarriage rates when follicle maturing drugs are used for those with regular menses but follicular maturation defects, or women with recurrent miscarriages. One mechanism of action seems to be related to production of an immunomodulatory protein, the progesterone-induced blocking factor either in the cytoplasm or in the circulation. PIBF inhibits cytotoxicity of natural killer cells. Cancer cells may 'borrow' the same mechanism to escape NK cell immunosurveillance.